Inhibition Effect of N-Hexane Extract of Cherry Mistletoe Leaves (Dendropthtoe pentandra (L) Miq.) on Xanthine Oxidase - Mario Saputra; Sadakata Sinulingga; Subandrate Subandrate (Biomedical Journal of Indonesia, 2024)
Introduction. Cherry leaf extract has been found to have the potentiality to impede the xanthine oxidase enzyme. It is believed that cherry mistletoe leaves also possess similar properties as they are hemiparasites of their host. This study aims to determine the inhibition effect of N-Hexane extract of mistletoe cherry leaves on the xanthine oxidase. Methods. This research was conducted as an experimental in-vitro study. Cherry mistletoe leaves were extracted by N-Hexane solvent. The extract was divided into five doses, i.e. 40 mg/L, 20 mg/L, 10 mg/L, 5 mg/L, and 2.5 mg/L. Phytochemical screening was conducted to identify secondary metabolites. The impact of xanthine oxidase inhibition was quantified using a UV-vis spectrophotometer at wavelength of 400 nm. Results. N-Hexane extract of cherry mistletoe leaves contains alkaloids and triterpenoids. N-Hexane extract of mistletoe cherry leaves at a dose of 40 mg/L, 20 mg/L, 10 mg/L, 5 mg/L, and 2.5 mg/L was able to inhibit the xanthine oxidase enzyme with the line equation y = -0.2543x+ 91.305. The IC50 value for the N-Hexane extract of cherry mistletoe leaves is 162 mg/L Conclusion. N-Hexane extract of cherry mistletoe leaves has the potency to inhibit the xanthine oxidase enzyme in the medium category.